2007
DOI: 10.1016/j.jmb.2006.10.080
|View full text |Cite
|
Sign up to set email alerts
|

The Conformations of the Manganese Transport Regulator of Bacillus subtilis in its Metal-free State

Abstract: The manganese transport regulator (MntR) from Bacillus subtilis binds cognate DNA sequences in response to elevated manganese concentrations. MntR functions as a homodimer that binds two manganese ions per subunit. Metal binding takes place at the interface of the two domains that comprise each MntR subunit: an N-terminal DNA-binding domain and a C-terminal dimerization domain. In order to elucidate the link between metal binding and activation, a crystallographic study of MntR in its metal-free state has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 33 publications
6
41
0
Order By: Relevance
“…In a very recent study, a similar scenario for a member of the single domain family, MntR was proposed based on crystallographic results (45). DeWitt et al showed that MntR has a conformational distribution of the DNA binding sites in the apo form.…”
Section: Discussionmentioning
confidence: 97%
“…In a very recent study, a similar scenario for a member of the single domain family, MntR was proposed based on crystallographic results (45). DeWitt et al showed that MntR has a conformational distribution of the DNA binding sites in the apo form.…”
Section: Discussionmentioning
confidence: 97%
“…6A) against H–D exchange relative to the apo-state 59 and limits the conformational disorder of the DNA-binding domain relative to the dimerization domain. 24 In any case, what seems clear is that direct coordination by M8 in DtxR/IdeR and D7 in MntR by the activating metal drives a global “caliper-like” closure of the DNA-binding domains in each subunit relative to one another (Supplementary Fig. S1), which brings them into alignment to bind to successive major grooves in the DNA operator.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The three most extensively studied members of this family are the homologous Fe(II)-sensors Corynebacterium diphtheriae DtxR and Mycobacterium tuberculosis IdeR 22,23 and Mn(II)-sensor in Bacillus subtilis, MntR. 2431 Although similar in both primary structure and quaternary structure of the activated metal-bound forms (see Supplementary Fig. S1), DtxR and MntR induce transcriptional co-repression by binding their cognate metal ions in distinct ways.…”
Section: Introductionmentioning
confidence: 99%
“…The conformation of Mn 2ϩ -bound MntR differs from the Zn 2ϩ -bound conformation with respect to the occupancy of the metal binding sites: Mn 2ϩ binds to two sites, whereas only one Zn 2ϩ ion binds to MntR, which does not allow binding of a second one (36). Metal binding at the second site is proposed to be required for DNA binding, as it promotes a disorder-to-order transition of MntR structure (17). PsaR shares 25% and 15% sequence identity with DtxR and MntR, respectively.…”
Section: Discussionmentioning
confidence: 99%